Eroding Mental Proliferation with the Buddhist Mindfulness Curriculum in Adult Education: The Ethnography of Interfaith Meditation - Prastowo, Fuji Riang (Universitas Muhammadiyah Surakarta, 2023)
The stressful adult phase in life encourages the emergence of mental illnesses such as anxiety and depression. From the Buddhist perspective, the root of depression in adulthood is due to Papancha or mental proliferation, which comes from three bases, namely Tanha (craving), Mana (Conceit), and Ditthi (wrong view). This article uses ethnography from the researcher's reflection notes as a meditation teacher who reconstructs the Buddhist mindfulness curriculum for interfaith meditators. The data collection technique uses contemplative stages with meditation practice, mapping of mind disturbances during meditation, and reflecting on overcoming Papancha with Abhidhamma. This article concludes that first, the differences in Western education are cognitively based in Neoliberalism, while meditation as a universal method is based on the inners. Second, mental proliferation in adulthood is due to the difficulty of living mindfully